Valores morais na escola para colher é preciso semear e cultivar - Borges, Graziella Diniz (Editora Oficina Universitária, 2020)
This work addresses Education in Values in young students, measuring their presence and the form of adherence in the school environment. It presents theories and concepts of Moral Education. Discusses moral values: Respect, Justice, Solidarity and Democratic Coexistence. Works on the moral and ethical planes, proposes paths for a democratic education, relating moral values to the profile of young people and the school context studied; collaborates with the reflection of undergraduate students in Pedagogy, Psychology, teachers, managers, as well as educational institutions interested in offering a Comprehensive Education for our young people and children.